2012
DOI: 10.9790/3013-0220322333
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Studies on Canine Mammary Tumour and its Relevance for Breast Cancer Studies

Abstract: Breast cancer is the most common cancer in women. Its incidence is rising globally and more so in the developing countries. There is a need to look for suitable animal model for biomedical research and pharmaceutical trails for this dreadly disease. In this pursuit, huge naturally occurring resource of canine mammary tumour may provide valid answer to impending questions in a shorter time frame. However, the epidemiology of canine mammary tumour (CMT) is poorly documented, especially in India. The present revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 40 publications
1
25
2
3
Order By: Relevance
“…Few data are available on the value of cytologic examination as a diagnostic or prognostic tool for mammary tumors in dogs. FNAC is considered a fast, accurate and cost-effective method for the diagnosis of human mammary tumours [8-11]. However, the evaluation of its accuracy is poorly reported in veterinary medicine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few data are available on the value of cytologic examination as a diagnostic or prognostic tool for mammary tumors in dogs. FNAC is considered a fast, accurate and cost-effective method for the diagnosis of human mammary tumours [8-11]. However, the evaluation of its accuracy is poorly reported in veterinary medicine.…”
Section: Discussionmentioning
confidence: 99%
“…To make a diagnosis, a number of clinical and paraclinical tests are used because it is essential to find the most aggressive malignant tumors that need radical surgery and supplementary treatment as soon as possible. After excision, a hematoxylin-eosin stain is often used to provide a histopathological diagnosis, but even though this is performed by experienced pathologists, the disorderly structure of some mammary tumors may cause confusion and may lead to an erroneous diagnosis of malignancy [8-11]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bei der intakten HĂŒndin galten Mammatumoren (MT) bislang als hĂ€ufigste Tumorerkrankung, wobei rund ein Drittel bis die HĂ€lfte der MT maligner Natur sind (13,38). In neueren Artikeln variieren die Angaben zur Mammatumorinzidenz mit 0,2 bis 112 FĂ€llen pro 10000 Dog Years at Risk erheblich, was Unterschiede im Studiendesign, in der Rasse-und Alterszusammensetzung sowie in der Reproduktionskontrollstrategie der untersuchten Populationen widerspiegelt (27,33,43,53). Eine PrĂ€disposition wird fĂŒr kleinere Rassen wie Dackel, Yorkshire Terrier, Malteser, Papillon oder Zwergspitz, aber auch fĂŒr kleine bis mittelgroße Spanielrassen und den Boxer beschrieben (40,57,69).…”
Section: Mammatumorenunclassified
“…The mammary glands in dogs are modified skin glands located bilaterally on the ventral surface of the animal from the cranial thorax to the perivulvar area which comprises of cranial thoracic, caudal thoracic, cranial abdominal, caudal abdominal, and inguinal glands from cranial to caudal region [ 1 , 2 ]. Surgery is the basic treatment for dogs with the most common type of mammary gland tumors (benign mixed tumor, adenoma, and adenocarcinoma), and adjuvant therapies (radiotherapy and chemotherapy) are used for inoperable tumors and also in inflammatory carcinoma [ 3 - 5 ]. The various surgical procedures have been described for the dogs ranging from local excision (simple mastectomy) to radical excision (radical mastectomy) and were found that there was no difference in recurrence rates and survival times following surgery [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%